2017
DOI: 10.1590/0001-3765201720160760
|View full text |Cite
|
Sign up to set email alerts
|

Sampling procedures for inventory of commercial volume tree species in Amazon Forest

Abstract: The spatial distribution of tropical tree species can affect the consistency of the estimators in commercial forest inventories, therefore, appropriate sampling procedures are required to survey species with different spatial patterns in the Amazon Forest. For this, the present study aims to evaluate the conventional sampling procedures and introduce the adaptive cluster sampling for volumetric inventories of Amazonian tree species, considering the hypotheses that the density, the spatial distribution and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…In these forests, the decline in associations for mature trees is expected due to local competition (Lan et al, 2012). Therefore, as a mature forest with high species diversity (Péllico Netto et al, 2017), the relationship between adult trees in the study area is less evident, confirming the results found.…”
Section: Spatial Interactions Among Populationssupporting
confidence: 83%
See 2 more Smart Citations
“…In these forests, the decline in associations for mature trees is expected due to local competition (Lan et al, 2012). Therefore, as a mature forest with high species diversity (Péllico Netto et al, 2017), the relationship between adult trees in the study area is less evident, confirming the results found.…”
Section: Spatial Interactions Among Populationssupporting
confidence: 83%
“…Flona do Jamari was the first public forest in Brazil to adopt the governments's system of forest concession for lumber production through Sustainable Forest Management (Bauch, Sills, Rodríguez, Mcginley, & Cubbage, 2009). The said forest is characterized by large diversity and richness of species with commercial size which occupy the upper levels and clear dominance of some lumber species (Péllico Netto, Pelissari, Cysneiros, Bonazza, & Sanquetta, 2017).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…the enumeration of all trees in the target area, is not always feasible due to operational limitations (Scolforo and Mello 1993). Such survey processes involve a number of statistical techniques and methods used to estimate important forest parameters with well-delimited errors (Scolforo and Mello 1993;Sanquetta et al 2014;Péllico Netto et al 2017). In this scenario, a commendable forest inventory is reached through a good sampling process choice.…”
Section: Introductionmentioning
confidence: 99%
“…The Maltese cross unit technique, which is a case of the two-stage cluster sampling, introduced by Péllico Netto and Brena (1997), has become a cornerstone in Brazilian national forest inventory methodology (Sanquetta et al 2014). Studies focusing on the comparison of different sampling techniques are scarce (Ubialli et al 2009;Motz et al 2010;Dalla Corte et al 2013;Baraloto et al 2013;Péllico Netto et al 2017), yet they are paramount to the identification of techniques best suited for data exploitation in tropical forests, with far-reaching consequences for the efficacy of public policies and strategies for forest stock management, as well as for ecological research of species of interest (Péllico Netto et al 2017).…”
Section: Introductionmentioning
confidence: 99%